Quality monitoring technology of MPEG2-TS VBR video stream - Peilin XUE; Jie LIANG; Xuebo WU (Dianxin kexue)
MPEG2-TS VBR coding technology is widely used,but the traditional MDI-DF-based algorithm is not suitable for detecting the transmission quality of VBR stream.The MPEG2-TS VBR stream quality evaluation algorithm was proposed.By monitoring the PCR field of MPEG2-TS stream,the absolute amount of playback time and unit time of VBR video stream received in unit time was calculated.VBR video streaming quality was evaluated according to the absolute deviation.Experimental results show that the proposed algorithm is feasible and effective.